"We have even locked out the very Zeitgeist itself ": Fraternal Discourse in Contemporary Norway. (13th February 2018) - Rostad, Aslak
Abstract : This article analyses the discourse employed by Norwegian fraternal organizations, based on Hugh B. Urban's postulate that secrecy is a strategy for 'adornment', i.e. conveying a special status to certain values and beliefs. The discourse is analysed in terms of the fraternities' idea of reality, identity, and mission, and claims that these organizations regard themselves as defenders of society's core values which they claim are threatened by moral corruption and decay.